Chloroplastic and nuclear diversity of wild beets at a large geographical scale: Insights into the evolutionary history of the Beta section. Issue 5 (14th February 2018) - Touzet, Pascal; Villain, Sarah; Buret, Laetitia; Martin, Hélène; Holl, Anne‐Catherine; Poux, Céline; Cuguen, Joël
Abstract: Historical demographic processes and mating systems are believed to be major factors in the shaping of the intraspecies genetic diversity of plants. Among Caryophyllales, the Beta section of the genus Beta, within the Amaranthaceae/Chenopodiaceae alliance, is an interesting study model with species and subspecies ( Beta macrocarpa, Beta patula, Beta vulgaris maritima and B.v. adanensis) differing in geographical distribution and mating system. In addition, one of the species, B. macrocarpa, mainly diploid, varies in its level of ploidy with a tetraploid cytotype described in the Canary Islands and in Portugal. In this study, we analyzed the nucleotide diversity of chloroplastic and nuclear sequences on a representative sampling of species and subspecies of the Beta section (except B. patula ). Our objectives were (1) to assess their genetic relationships through phylogenetic and multivariate analyses, (2) relate their genetic diversity to their mating system, and (3) reconsider the ploidy status and the origin of the Canarian Beta macrocarpa . Abstract : In this study, we analyzed the nucleotide diversity of chloroplastic and nuclear sequences on a representative sampling of species and subspecies of the Beta section. Our objectives were (1) to assess their genetic relationships through phylogenetic and multivariate analyses, (2) relate their genetic diversity to their mating system, and (iii) reconsider the ploidy status and the origin of the Canarian Beta macrocarpa .